Understanding the thermal instability of fluoroethylene carbonate in LiPF6-based electrolytes for lithium ion batteries. (20th January 2017) - Kim, Koeun; Park, Inbok; Ha, Se-Young; Kim, Yeonkyoung; Woo, Myung-Heuio; Jeong, Myung-Hwan; Shin, Woo Cheol; Ue, Makoto; Hong, Sung You; Choi, Nam-Soon
Graphical abstract: Highlights: The FEC in LiPF6 -based electrolytes thermally decomposes at elevated temperatures. Lewis acids in the electrolyte promote de-fluorination of the FEC to form HF. The HF causes the SEI destruction and severe metal ion dissolution from the cathode. Abstract: The cycling and storage performances of LiCoO2 (LCO)-LiNi0.5 Co0.2 Mn0.3 O2 (NCM)/pitch-coated silicon alloy-graphite (Si-C) full cells with ethylene carbonate (EC)–based and fluoroethylene carbonate (FEC)–based electrolytes are investigated at elevated temperatures. Excess FEC (used as a co-solvent in LiPF6 -based electrolytes), which is not completely consumed during the formation of the solid electrolyte interphase (SEI) layer on the electrodes, is prone to defluorination in the presence of Lewis acids such as PF5 ; this reaction can generate unwanted HF and various acids (H3 OPF6, HPO2 F2, H2 PO3 F, H3 PO4 ) at elevated temperatures. Our investigation reveals that the HF and acid compounds that are formed by FEC decomposition causes significant dissolution of transition metal ions (from the LCO-NCM cathode) into the electrolyte at elevated temperatures; as a result, the reversible capacity of the full cells reduces because of the deposition of the dissolved metal ions onto the anode. Moreover, we demonstrate possible mechanisms that account for the thermal instability of FEC in LiPF6 -based electrolytes at elevated temperatures using model experiments.